The Land of Stories. Beyond the kingdoms - Colfer, Chris, 1990- (Colfer, Chris, 1990- Land of Stories, 2015)
"The Masked Man possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains! So begins a race through the magical Land of Oz, the fantastical world of Neverland, the madness of Wonderland, and beyond. Can twins Alex and Conner catch up to the Masked Man?"--